2011
DOI: 10.1002/ijc.25929
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking during pregnancy and childhood lymphoma: A meta‐analysis

Abstract: Results from epidemiological studies exploring the association between childhood lymphoma and maternal smoking during pregnancy have been contradictory. This meta-analysis included all published cohort (n 5 2) and case-control (n 5 10) articles; among the latter, the data of the Greek Nationwide Registry for Childhood Hematological Malignancies study were updated to include all recently available cases (-2008). Odds ratios (ORs), relative risks and hazard ratios were appropriately pooled in three separate anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 48 publications
0
17
1
2
Order By: Relevance
“…This can partly be explained by the fact that we excluded several original studies included in their work, since the study populations overlapped with bigger, epidemiological studies, which were published after Boffetta’s meta-analysis was reported. A meta-analysis focusing on childhood lymphoma reported increased risk for non-Hodgkin lymphoma, but it did not suggest any association with Hodgkin lymphoma or all lymphoma types combined [98]. In our analysis, non-Hodgkin’s lymphoma and any other type of lymphoma were associated with maternal smoking.…”
Section: Discussioncontrasting
confidence: 81%
“…This can partly be explained by the fact that we excluded several original studies included in their work, since the study populations overlapped with bigger, epidemiological studies, which were published after Boffetta’s meta-analysis was reported. A meta-analysis focusing on childhood lymphoma reported increased risk for non-Hodgkin lymphoma, but it did not suggest any association with Hodgkin lymphoma or all lymphoma types combined [98]. In our analysis, non-Hodgkin’s lymphoma and any other type of lymphoma were associated with maternal smoking.…”
Section: Discussioncontrasting
confidence: 81%
“…Consistent with a previous meta-analysis published in 2002 [43], our meta-analysis also found no association between maternal smoking during pregnancy and the risk of CBT. Previous studies have reported that maternal smoking during pregnancy is a possible risk factor for stillbirth [44], child overweight [45] and childhood NHL [46] but not for childhood HL [46], leukemia [47] or testicular cancer [48]. Therefore, maternal smoking may have different effects on offspring through multiple mechanisms, specific and non-specific.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that exposures during the prenatal period, which is a highly vulnerable period of development (3, 4), may contribute to development of pediatric lymphoma. (5, 6)…”
Section: Introductionmentioning
confidence: 99%